Insensitive Investors - Constantin Charles; Cary D. Frydman; Mete Kilic (Center for Economic Studies and ifo Institute (CESifo), 2022)
We show theoretically that the weak transmission of beliefs to actions induces a strong bias in basic asset pricing tests. In particular, expected returns can appear to decline in risk when investors weakly transmit their payoff expectations into willingness to pay. We experimentally test this prediction and find that subjects exhibit an extremely weak transmission of beliefs to actions, which generates a negative risk-return relation. We argue that the weak transmission is due to cognitive noise and demonstrate that cognitive noise causally affects the risk-return relation. Our results highlight the importance of incorporating weak transmission into belief-based asset pricing models.
Keywords: 330; investor behavior; cognitive noise; portfolio choice